Andersen's model on determining the factors associated with antenatal care services in Nepal: an evidence-based analysis of Nepal demographic and health survey 2016 - Bidusha Neupane; Sujan Rijal; Srijana G.C; Til Bahadur Basnet (BMC, 2020)
Abstract Background With the formulation of the National Safe Motherhood Policy in 1998, safe motherhood has forever been a priority program in Nepal. Under the safe motherhood program, every woman is provided with essential maternal health care services until now through the four-tire district health care system. There is a considerable increase in the utilization of antenatal care (ANC) by a skilled health provider from 2011 to 2016, 58 to 84%, respectively. However, inequality, exclusion, and under-utilization in health care services continue in many regions of Nepal. The present study aimed to explore the different types of socio-demographic factors associated with current ANC service utilization in Nepal. Methods A cross-sectional study was conducted using the Nepal Demographic and Health Surveys data (DHS-7, 2016-2017). We estimated the latest pregnancy and live births in recent 5 years with the utilization of ANC services, and socio-economic differentials in these indicators under the framework of the Andersen behavioral model. Results Two in three (69.8%) with last birth accessed at least four ANC visits. The rate of live birth was about 98.6% in the ANC4+ group, higher than that of 96.8% in the ANC4- group (χ2: 14.742, P <  0.001). In the multilevel logistic regression analysis, we found that women from province 2 (OR: 0.48; 95%CI: 0.32-0.74) and province 6 (OR: 0.46; 95%CI: 0.30-0.71) were significantly less likely to visit ANC 4 or more times. Age (OR: 0.95; 95%CI: 0.93-0.96) was also significantly associated with the frequency of ANC visits. Level of Women's education and education of her partner were both significantly associated with the ANC visits: women (OR: 4.64; 95%CI: 3.05-7.05) and her partner (OR: 1.45; 95%CI: 1.01-2.06) having higher education were most likely to go for the recommended number of ANC visits. Moreover, women having exposure to multimedia were more likely to go for four or more ANC check-ups. Conclusions The results highlight the need for governments and health care providers to develop special health promotion program with a focus on the vulnerable and disadvantaged and to use multi-media for maternal health literacy improvement flexibly, and maternal health system strengthening.